2015
DOI: 10.1175/mwr-d-14-00279.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Real-Data Simulations of the 3 May 1999 Oklahoma City Tornadic Supercell and Associated Tornadoes to Multimoment Microphysics. Part I: Storm- and Tornado-Scale Numerical Forecasts

Abstract: Numerical predictions of the 3 May 1999 Oklahoma City, Oklahoma, tornadic supercell are performed within a real-data framework utilizing telescoping nested grids of 3-km, 1-km, and 250-m horizontal spacing. Radar reflectivity and radial velocity from the Oklahoma City WSR-88D are assimilated using a cloud analysis procedure coupled with a cycled 3DVAR system to analyze storms on the 1-km grid for subsequent forecast periods. Single-, double-, and triple-moment configurations of a multimoment bulk microphysics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…Simulated hydrometeor fields, precipitation, and storm dynamics are quite sensitive to the choice of the microphysics scheme. Several studies have demonstrated the advantages of multimoment schemes over one‐moment scheme [e.g., Milbrandt and Yau , ; Morrison et al ., ; Dawson et al ., , ; Bryan and Morrison , ]. For example, Dawson et al .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Simulated hydrometeor fields, precipitation, and storm dynamics are quite sensitive to the choice of the microphysics scheme. Several studies have demonstrated the advantages of multimoment schemes over one‐moment scheme [e.g., Milbrandt and Yau , ; Morrison et al ., ; Dawson et al ., , ; Bryan and Morrison , ]. For example, Dawson et al .…”
Section: Introductionmentioning
confidence: 84%
“…Simulated hydrometeor fields, precipitation, and storm dynamics are quite sensitive to the choice of the microphysics scheme. Several studies have demonstrated the advantages of multimoment schemes over one-moment scheme [e.g., Milbrandt and Yau, 2006a;Morrison et al, 2009;Dawson et al, 2010Dawson et al, , 2015Bryan and Morrison, 2012]. For example, Dawson et al [2010] found that a multimoment scheme produced improved predictions of supercell storm cold pool size and strength, and reflectivity structure, particularly in the forward flank region of the storm.…”
Section: Introductionmentioning
confidence: 99%
“…Many challenges still remain for PRD assimilation. The 20 May study demonstrated how the number of predicted moments in model microphysics schemes affect microphysical processes, where excessive size sorting known to occur with double moment microphysics schemes (Dawson et al, 2010;Morrison and Milbrandt, 2011;Dawson et al, 2015) had a significant impact on the effectiveness of PRD data assimilation. Also, the forward operators and microphysics schemes must be improved, specifically in regard to the treatment of frozen hydrometeors as well as mixed-phase hydrometeors, which most microphysics schemes do not predict.…”
Section: An Example Of Da Analysis With Prdmentioning
confidence: 99%
“…Using numerical simulations to explore the range of thermodynamic characteristics within storms is problematic as well, owing to the great sensitivity of the temperature and precipitation fields to the microphysics parameterization (e.g., Gilmore et al 2004;Snook and Xue 2008;Dawson et al 2010Dawson et al , 2015Bryan and Morrison 2012). It is not a stretch to say that an investigator can obtain almost any lowlevel buoyancy field in a simulated thunderstorm that she or he wants, simply by tuning the models microphysics parameterization.…”
Section: Aboveground Thermodynamic Observations In Convective Storms mentioning
confidence: 99%